PENGEMBANGAN E-MODUL MENGGUNAKAN 3D PAGEFLIP PROFESSIONAL UNTUK MEREMEDIASI MISKONSEPSI SISWA SMP PADA MATERI TEKANAN ZAT CAIR - Amelia, Elga Amelia; Maison, Maison; Kamid, Kamid (EduFisika: Jurnal Pendidikan Fisika, 2021)
The purpose of this study was to develop an e-module on liquid pressure material to remediate students' misconceptions. This type of research is development research using the ADDIE model. Data collection techniques used questionnaires for validators, teachers and students as well as four-tier diagnostic tests. The effectiveness test was obtained from the analysis of the students' pre-test and post-test results based on the four tier diagnostic test decision criteria. Based on the results of the validation of the e-module development by material experts and media experts, it was declared feasible, while the results of the teacher's response obtained a percentage of 85.71% in the very good category, the results of student responses in the one-on-one trial obtained a percentage of 92.67% in the very good category. , the results of student responses in small group trials obtained a percentage of 88.41% in the very good category. The results of the student effectiveness test experienced a significant decrease in misconceptions with an average percentage of 52%. Wilcoxon nonparametric test results show the results of z = -2,673 and Asymp.sig (2-tailed) is 0.008, it can be concluded that there is a significant difference between students' pre-test and post-test scores, so it can be concluded that the use of e-modules is effective in remediating students' misconceptions. SMP and based on the effect size value of r = 0.63, which means that the use of e-modules has a moderate effect in remediating students' misconceptions about the material pressure of liquids.